Spatial Development Tendencies and Emergence of New Industrial Districts in Turkey in the Post-1980 Era - Metin Ozaslan (European Regional Science Association (ERSA), 2006)
The aim of this paper is to analyse the changing macro-economic policies and their spatial impacts on the economic geography of Turkey after 1980's. The first section of the chapter is focused on the two main macro-economic policies namely inward-oriented development strategy prior to the year of 1980 and the outward-oriented development strategy after 1980. In the second section of the article regional disparities and the regional development policies in Turkey are briefly discussed. In the next section spatial effects of the outward oriented policies are analysed focusing on the spatial distribution of industry. Industrial shifts indicate that there are mainly four spatial development tendencies in Turkey namely, the rise of metropolitan cities as service centres, the industrial growth of hinterland provinces that are neighbouring cities around metropolitan cities on the basis of decentralising industry, the decline of economic activities in the provinces in which state economic enterprises are common, and the emergence of the new industrial districts/ cities on the basis of SMEs' networks and sectoral specialisation. The last section of the paper analyses the emergence of new industrial districts in Turkey focusing on the main features of five territorial cities namely Denizli, Gaziantep, Çorum, Kayseri and Kahramanmaraþ. It is concluded that the new industrial districts developed on the basis of SME clusters have crushed the spatial development trends in Turkey based on metropolitan cities and they have conveyed the development dynamics to small and medium sized Anatolian cities. The districts that have followed a development path within the framework of their own endogenous potentials have succeeded in becoming a centre of attraction and have started to serve a significant function in the transfer of development to the less developed Anatolia. By disrupting the unbalanced development tendencies on the national level, emerging around a few growth poles, they have yielded an alternative development tendency against the polarised development tendencies.
Keywords: 330